ISOLATION, IDENTIFICATION AND ENZYME PRODUCTION PROFILE OF A. NIGER - N. Akhtar; A. Shoaib; S. Munir; A. Ali; S. Khurshid (Journal of Animal and Plant Sciences, 2014)
Black Aspergilli (Aspergillus section Nigri) have agricultural and industrial importance. Several species of this group are recognized human pathogens and some are mycotoxin producers. Despite of their wide use in teaching and research, taxonomy of this group remains unclear due to very close morphological features. Present study is aimed to distinguish Aspergillus niger strains that were isolated from fruits and vegetables by utilizing morphological, physiological and molecular approaches. Results demonstrated that micro- and macro-morphological characters of A. niger isolates were similar and strains were very close to each other on the basis of rDNA spacer sequence also. The most interesting finding of this study was that the production and activity of catalase, pectinase, lipase and urease enzymes by different isolates that were similar morphologically as well as genetically, was very different.
Keywords: Taxonomy; morphology; enzyme; molecular characterization; Internal transcribe spacer